Identification of Emerging Human Mastitis Pathogens by MALDI-TOF and Assessment of Their Antibiotic Resistance Patterns - María Marín (Frontiers in Microbiology, 2017)
Lactational mastitis constitutes one of the main causes of undesired weaning, depriving the mother–infant pair from the benefits of breastfeeding; therefore, this condition should be considered a relevant public health issue. The role of specific microorganisms remains unclear since human milk cultures and antibiotic susceptibility testing (AST) are not routinely performed, despite the fact that this would be key to ensure an early and effective diagnosis and treatment. The objective of this study was to describe the culturable microbial diversity in 647 milk samples from breastfeeding women with clinical symptoms of mastitis by Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF) VITEK MS technology and to analyze the antimicrobial susceptibility profiles of a collection of isolates from these samples by the VITEK 2 AST system. Staphylococcus epidermidis was the most common species isolated from mastitis samples (87.6%), while Staphylococcus aureus was detected in 22.1%. Streptococci constituted the second (68.6%) most prevalent bacterial group, with Streptococcus mitis/oralis, Streptococcus salivarius, and Streptococcus parasanguinis detected with frequencies of 40.8, 36.8, and 14.4%, respectively. The antibiotic susceptibility profiles of 642 staphylococcal isolates indicated a remarkable resistance to benzylpenicillin (88.3%) and erythromycin (67.3%) with differences between species. A high percentage of Staphylococcus isolates were resistant to at least one antibiotic (Staphylococcus hominis, 100%; S. epidermidis, 98.2%; S. aureus, 92.9%; Staphylococcus lugdunensis, 90.5%) and the percentage of multidrug-resistance (MDR) isolates was noticeable (S. hominis, 81%; S. epidermidis, 64.4%; S. aureus, 11.5%; S. lugdunensis, 10.5%). In relation to streptococcal isolates (n = 524), AST revealed high or moderate percentages of resistance to erythromycin (68.7%), benzylpenicillin (63.7%), ampicillin (51.5%), and tetracycline (30.8%). Antibiotic resistance to at least one antibiotic was detected in 97.6% of S. parasanguinis, 92.6% of S. salivarius, 83.3% of S. mitis/oralis, and 72.4% of Streptococcus vestibularis isolates. A significant number of MDR streptococcal isolates was also found (S. parasanguinis, 51.2%; S. salivarius, 39.3%; S. mitis/oralis, 34.6%; and S. vestibularis, 19%). The results highlight the important role of coagulase-negative staphylococci and streptococci as human mastitis-causing agents. Moreover, the high rates of antimicrobial resistance among these microorganisms must be contemplated as an issue of clinical relevance in relation to treatment options.